A study of the adoption of quality programs and tools at companies with ISO 9001 certification: multiple case studies - Nadae, Jeniffer de; Oliveira, José Augusto de; Oliveira, Otávio José de (Revista Gestão da Produção Operações e Sistemas, 2012)
The ISO 9001 certification process has gained increasing importance for organizations seeking to achieve benefits related to productivity, quality of products and processes, and to increase market share. In order to maintain certi-fication benefits organizations adopt quality programs and tools according to their needs for achieving continuous improvement in organizational processes. The study aims at identifying the most used quality programs and tools and the benefits and difficulties encountered by organizations during implementation of Quality Management Systems and the ISO 9001 certification process. The qualitative method was adopted for this study through multiple case studies with companies in the printing sector, automotive batteries, car parts, machine parts and equipment. These firms are located in two cities in the state of São Paulo, Bauru and Sorocaba. It can be concluded that adoption of quality programs and tools is very important for maintaining quality management. The most used programs and tools at the researched enterprises are 5S, Pareto Chart and the Ishikawa Diagram, while benefits and difficulties vary according to the organization’s segment and history. However, it is possible to see that there are many quality programs and tools available in literature, but few are used by companies.Keywords: Quality Management; ISO 9001 Certification; Quality Programs and Tools